Research and Design Idea of a New Type of Power Supply System of Central Substation of Coal Mine - YANG Wei-yi (Gong-kuang zidonghua, 2010)
A design idea of new type of power supply system of central substation of coal mine was proposed on the basis of analyzing existing technology status of power supply system of central substation of coal mine. The power supply system is mainly used to solve problem of reliability of control power supply of distribution devices of central substation of coal mine. The actual application showed that the system can make high-vacuum electric distributor of central substation of coal mine operate accurately and reliably.